Residual mucin and response after neoadjuvant chemotherapy (NAC) in breast cancer. (6th May 2016) - Jove, Maria; Verghese, Eldo; Sharma, Nisha; Lane, Sally
Abstract : Neoadjuvant chemotherapy (NAC) is the standard of care for patients with breast cancer with inoperable disease or smaller tumours who might benefit from a conservative surgery after downstaging of their disease. Nevertheless, evidence shows that preoperative and postoperative chemotherapy are equivalent in terms of long-term survival. Response and histological changes after NAC have been widely studied in invasive ductal carcinoma not otherwise specified, but there is a paucity of characterisation of patterns of response to chemotherapy in less frequent histological types. We report extensive residual mucin deposits after chemotherapy in a woman with locally advanced breast cancer and a prominent mucinous component at diagnosis. Interestingly, residual mucin was co-located with the initial tumour, in the breast as well as in the axillary lymph nodes. The distribution of mucin may be a valuable marker of the extent of mucinous carcinomas prior to NAC.